2018
DOI: 10.3390/e20110835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiation Response in CoCrFeCuNi High-Entropy Alloys

Abstract: CoCrFeCuNi high-entropy alloys (HEAs) prepared by arc melting were irradiated with a 100 keV He+ ion beam. Volume swelling and hardening induced by irradiation were evaluated. When the dose reached 5.0 × 1017 ions/cm2, the Cu-rich phases exhibited more severe volume swelling compared with the matrix phases. This result indicated that the Cu-rich phases were favorable sites for the nucleation and gathering of He bubbles. X-ray diffraction indicated that all diffraction peak intensities decreased regularly. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…On the other hand, Wang et al [308] noticed a reduction in crystallinity resulted from He ion irradiation on CoCrFeCuNi alloy. Yang et al [298] observed that precipitation of the L12 phase was suppressed due to irradiation-induced ballistic mixing at temperatures less than or equal to 500 • C. Additionally, precipitation of the B2 phase was favored at 650 • C due to improved diffusion by irradiation.…”
Section: Phase Stabilitymentioning
confidence: 99%
“…On the other hand, Wang et al [308] noticed a reduction in crystallinity resulted from He ion irradiation on CoCrFeCuNi alloy. Yang et al [298] observed that precipitation of the L12 phase was suppressed due to irradiation-induced ballistic mixing at temperatures less than or equal to 500 • C. Additionally, precipitation of the B2 phase was favored at 650 • C due to improved diffusion by irradiation.…”
Section: Phase Stabilitymentioning
confidence: 99%
“…As a result, HEAs have shown excellent performance in radiation resistance, which provides new ideas for the development of nuclear materials. CoCrFeCuNi alloys were irradiated with a 100 keV He + ion beam by Wang et al [ 49 ]. It was indicated that Cu-rich phases were favorable sites for the nucleation and gathering of He bubbles.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Wang et al [29] studied the irradiation of CoCrCuFeNi HEA under different dose of He+ ion beam. Kumar et al [30] investigate the radiation resistance of CrFeMnNi and FeCrNi.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 This could be attributed to their lattice distortion and sluggish diffusion effects, 25–28 which reduce the migration and diffusion of defects. Wang et al 29 studied the irradiation of CoCrCuFeNi HEA under different doses of He + ion beams. Kumar et al 30 investigated the radiation resistance of CrFeMnNi and FeCrNi.…”
Section: Introductionmentioning
confidence: 99%